2016
DOI: 10.1016/j.biopen.2016.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Na+/H+ exchange and cell effector functionality in metastatic breast cancer

Abstract: Metastasis is the leading cause of mortality in patients with breast cancer. In triple-negative breast cancer, high recurrence rates, increased invasive capacity of cells, and their aggressive ability to metastasize at secondary sites dictate patient survival. The Na+/H+ exchanger isoform 1 (NHE1) plays a critical role in controlling the metastatic potential of these cells. Its activity results in an elevation of intracellular pH and in extracellular acidification, a key step in the establishment of the tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 31 publications
1
30
0
Order By: Relevance
“…Most importantly, a series of publications in this line have shown that the H + extrusion in BC cells, especially in triple-negative breast cancer (TNBC), is mainly mediated by NHE1 overexpression and H + -extrusion, with NHE1 being the real actor that induces a high pHi-mediated carcinogenic effect on breast cells [ 44 ]. Furthermore, H + extrusion also is the main etiological mediator in the transition from ductal carcinoma in situ to invasive BC, where even a precancerous lesion already shows a higher than normal proton export rate [ 44 , 45 , 46 ] ( Figure 2 ). Most recently, the intricate relationships of tumor pHi and pHe with ion channels and changes in membrane potential have been widely discussed and reviewed [ 47 ].…”
Section: Breast Cancer Ph-related Etiology and Pathogenesis The mentioning
confidence: 99%
See 1 more Smart Citation
“…Most importantly, a series of publications in this line have shown that the H + extrusion in BC cells, especially in triple-negative breast cancer (TNBC), is mainly mediated by NHE1 overexpression and H + -extrusion, with NHE1 being the real actor that induces a high pHi-mediated carcinogenic effect on breast cells [ 44 ]. Furthermore, H + extrusion also is the main etiological mediator in the transition from ductal carcinoma in situ to invasive BC, where even a precancerous lesion already shows a higher than normal proton export rate [ 44 , 45 , 46 ] ( Figure 2 ). Most recently, the intricate relationships of tumor pHi and pHe with ion channels and changes in membrane potential have been widely discussed and reviewed [ 47 ].…”
Section: Breast Cancer Ph-related Etiology and Pathogenesis The mentioning
confidence: 99%
“…Most recently, however, other channels, transporters and even certain aquaporins (AQP), mainly AQP1 and AP3, as well as Cl − channels with Ca 2+ influx, have also been shown to be important in the initiation and progression of TNBC [ 49 , 50 ]. All these fundamental data clarify why and how NHE1, and its main consequences, H + extrusion and an elevated pHi, are involved in BC etiology, invasion, and the metastatic process, as well as in multiple drug resistance (MDR) [ 43 , 44 , 45 , 46 , 51 , 52 ]. While a pathologically elevated pHi should be considered to be the main responsible factor of BC-promoting activity, it secondarily induces a highly pathological and damaging extracellular/intratumoral TME with the final result of inducing CPR.…”
Section: Breast Cancer Ph-related Etiology and Pathogenesis The mentioning
confidence: 99%
“…Importantly, H+ extrusion alone has been implicated in the transition and progression from precancerous ductal carcinoma in situ to invasive BC. Of note, the precancerous lesion already shows a higher than normal proton export rate [36,38,102]. Indeed, the invasive BC cells show a higher pHi and a higher production and exportation of H + into the TME than noninvasive cells [36,97,105].…”
Section: Ph/nhe Microenvironmental Acidosis and Immunity Insulin Pmentioning
confidence: 96%
“…extrusion has a carcinogenic effect by itself on breast cells [36]. The same alteration also plays a fundamental role in the metastatic process and in multiple drug resistance (MDR) [37,38,102,103]. In these studies, NHE1 hyperactivity and/or a high pHi act as an early and decisive driver in BC carcinogenesis and also in most, if not all, other human malignancies [33,104].…”
Section: Ph/nhe Microenvironmental Acidosis and Immunity Insulin Pmentioning
confidence: 99%
See 1 more Smart Citation